SARS-CoV-2 (COVID-19) Pandemic Remains a Global Public Health Threat - Pal, Mahendra; Bulcha, Mati Roba; Milsan Getu Banu; Ketchakmadze, Dimitri (Zenodo, 2021)
Recently, an upsurge in the incidence of several emerging infectious diseases is causing great challenges to the health professionals throughout the globe. Since early 2020, an outbreak of coronavirus disease 2019 (COVID-19), now a pandemic, is hitting the world severely. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), causative agent of COVID-19, gain entry through the respiratory systems (nasopharyngeal) route causing infection. This disease is reported from all continents except Antarctica and it most commonly affects the lungs rather than the other organs. In affected person, pneumonia, cough, sore throat, dyspnea, fever, headache, and rhinorrhea is the main symptoms of COVID-19. There are different investigation methods to diagnose a patient suspected of COVID-19 like radiography and different laboratory technique like RT-PCR, which remains the investigation of choice. Social distancing, practicing hand hygiene, and use of facemask are mandatory to prevent the disease. Many of the drug trials are underway with the recent FDA approval of remdesivir. Very recently, immunization programme against COVID-19 is going on in many countries of the world. However, the efficacy and safety of the vaccines are not yet fully established. : {"references": ["S\u00e1nchez CM, Jim\u00e9nez G, Laviada MD, Correa I, Su\u00f1\u00e9 C, Bullido Mj, et al. Antigenic homology among coronaviruses related to transmissible gastroenteritis virus. Virology. 1990;174(2):410-7. doi: 10.1016/0042-6822(90)90094-8.", "Pal M, Kerorsa GB, Kandi V. A Knowledge Update on SARS-Coronavirus-2 (SARS-CoV-2)/COVID-19 and Its Global Public Health Implications. Am J Clin Med Res. 2020;8(1):23-7. doi: 10.12691/AJCMR-8-1-5.", "Su L, Ma X, Yu H, Zhang Z, Bian P, Han Y, et al. The different clinical characteristics of corona virus disease cases between children and their families in China - the character of children with COVID-19. Emerg Microbes Infect. 2020;9(1):707-13. doi: 10.1080/22221751.2020.1744483.", "Pal M, Berhanu G, Desalegn C, Kandi V. Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2): An Update. Cureus. 2020;12(3):e7423. doi: 10.7759/cureus.7423.", "Yuen KS, Ye ZW, Fung SY, Chan CP, Jin DY. SARS-CoV-2 and COVID-19: The most important research questions. Cell Biosci. 2020;10:40. doi: 10.1186/s13578-020-00404-4.", "Pal M, Berhanu Kerorsa G, Mahendra Pal P. Zoonotic Significance of COVID-19 and Precautions Related to Animals During Outbreak of the Disease. J One Health. 2020;8(2):39-43.", "Unhale SS, Ansar QB, Sanap S, Thakhre S, Wadatkar S. A review on Corona Virus (COVID-19). World J Pharm Life Sci. 2020;6(4):109-15.", "Weiss SR, Navas-Martin S. Coronavirus pathogenesis and the emerging pathogen severe acute respiratory syndrome coronavirus. Microbiol Mol Biol Rev. 2005;69(4):635-64. doi: 10.1128/MMBR.69.4.635-664.2005.", "Powell-Jackson T, King JJC, Makungu C, Spieker N, Woodd S, Risha P, et al. Infection prevention and control compliance in Tanzanian outpatient facilities: a cross-sectional study with implications for the control of COVID-19. Lancet Glob Health. 2020;8(6):e780-e789. doi: 10.1016/S2214-109X(20)30222-9.", "Rutayisire E, Nkundimana G, Mitonga HK, Boye A, Nikwigize S. What works and what does not work in response to COVID-19 prevention and control in Africa. Int J Infect Dis. 2020;97:267-9. doi: 10.1016/j.ijid.2020.06.024.", "Anjorin AAA. The coronavirus disease 2019 (COVID-19) pandemic: A review and an update on cases in Africa. Asian Pac J Trop Med. 2020;13(5):199-203. doi: 10.4103/1995-7645.281612.", "Zhang Y, Zhao Q, Hu B. Community-based prevention and control of COVID-19: Experience from China. Am J Infect Control. 2020;48(6):716-7. doi: 10.1016/j.ajic.2020.03.012.", "Chen Y, Liu Q, Guo D. Emerging coronaviruses: Genome structure, replication, and pathogenesis. J Med Virol. 2020;92(4):418-23. doi: 10.1002/jmv.25681.", "Di Gennaro F, Pizzol D, Marotta C, Antunes M, Racalbuto V, Veronese N, et al. Coronavirus Diseases (COVID-19) Current Status and Future Perspectives: A Narrative Review. Int J Environ Res Public Health. 2020;17(8):2690. doi: 10.3390/ijerph17082690.", "Hafeez A, Ahmad S, Ali Siddqui S, Ahmad M, Mishra S. A Review of COVID-19 (Coronavirus Disease-2019) Diagnosis, Treatments and Prevention. Eurasian J Med Oncol. 2020;4(2):116-25. doi: 10.14744/ejmo.2020.90853.", "Li X, Geng M, Peng Y, Meng L, Lu S. Molecular immune pathogenesis and diagnosis of COVID-19. J Pharm Anal. 2020;10(2):102-8. doi: 10.1016/j.jpha.2020.03.001.", "Zheng J. SARS-CoV-2: an Emerging Coronavirus that Causes a Global Threat. Int J Biol Sci. 2020;16(10):1678-85. doi: 10.7150/ijbs.45053.", "Jonsdottir HR, Dijkman R. Coronaviruses and the human airway: a universal system for virus-host interaction studies. Virol J. 2016;13:24. doi: 10.1186/s12985-016-0479-5.", "Song R, Han B, Song M, Wang L, Conlon CP, Dong T, et al. Clinical and epidemiological features of COVID-19 family clusters in Beijing, China. J Infect. 2020;81(2):e26-e30. doi: 10.1016/j.jinf.2020.04.018.", "Sahin AR, Erdogan A, Agaoglu PM, Dineri Y, Cakirci AY, Senel ME, et al. 2019 Novel Coronavirus (COVID-19) Outbreak: A Review of the Current Literature. Eurasian J Med Oncol. 2020;4(1):1-7. doi: 10.14744/ejmo.2020.12220.", "Lai AL, Millet JK, Daniel S, Freed JH, Whittaker GR. The SARS-CoV Fusion Peptide Forms an Extended Bipartite Fusion Platform that Perturbs Membrane Order in a Calcium-Dependent Manner. J Mol Biol. 2017;429(24):3875-92. doi: 10.1016/j.jmb.2017.10.017.", "Baloch S, Baloch MA, Zheng T, Pei X. The Coronavirus Disease 2019 (COVID-19) Pandemic. Tohoku J Exp Med. 2020;250(4):271-8. doi: 10.1620/tjem.250.271.", "G\u00fcner R, Hasano\u011flu I, Akta\u015f F. COVID-19: Prevention and control measures in community. Turk J Med Sci. 2020;50(SI-1):571-7. doi: 10.3906/sag-2004-146.", "Beigel JH, Tomashek KM, Dodd LE, Mehta AK, Zingman BS, Kalil AC, et al. Remdesivir for the Treatment of Covid-19 - Final Report. N Engl J Med. 2020;383(19):1813-26. doi: 10.1056/NEJMoa2007764.", "Shen J, Duan H, Zhang B, Wang J, Ji JS, Wang J, et al. Prevention and control of COVID-19 in public transportation: Experience from China. Environ Pollut. 2020;266(Pt 2):115291. doi: 10.1016/j.envpol.2020.115291.", "Ogunleye OO, Basu D, Mueller D, Sneddon J, Seaton RA, Yinka-Ogunleye AF, et al. Response to the Novel Corona Virus (COVID-19) Pandemic Across Africa: Successes, Challenges, and Implications for the Future. Front Pharmacol. 2020;11:1205. doi: 10.3389/fphar.2020.01205.", "Wise J. Covid-19: European countries suspend use of Oxford-AstraZeneca vaccine after reports of blood clots. BMJ. 2021;372:n699. doi: 10.1136/bmj.n699.", "Dyer O. Covid-19: EMA defends AstraZeneca vaccine as Germany and Canada halt rollouts. BMJ. 2021;373:n883. doi: 10.1136/bmj.n883.", "Mahase E. Covid-19: AstraZeneca vaccine is not linked to increased risk of blood clots, finds European Medicine Agency. BMJ. 2021;372:n774. doi: 10.1136/bmj.n774.", "Choi EM. COVID-19 vaccines for low- and middle-income countries. Trans R Soc Trop Med Hyg. 2021;115(5):447-56. doi: 10.1093/trstmh/trab045.", "Al-Qahtani WS, Alsafhi FA. A Commentary on Realities of Developing COVID-19 Vaccines Discussed through the Global Health Safety Perspective. Vaccines (Basel). 2021;9(3):274. doi: 10.3390/vaccines9030274.", "Iacobucci G, Mahase E. Covid-19 vaccination: What's the evidence for extending the dosing interval? BMJ. 2021;372:n18. doi: 10.1136/bmj.n18.", "Subbarao S, Warrener LA, Hoschler K, Perry KR, Shute J, Whitaker H, et al. Robust antibody responses in 70-80-year-olds 3 weeks after the first or second doses of Pfizer/BioNTech COVID-19 vaccine, United Kingdom, January to February 2021. Euro Surveill. 2021;26(12):2100329. doi: 10.2807/1560-7917.ES.2021.26.12.2100329.", "Shimabukuro T. Allergic reactions including anaphylaxis after receipt of the first dose of Pfizer-BioNTech COVID-19 vaccine - United States, December 14-23, 2020. Am J Transplant. 2021;21(3):1332-7. doi: 10.1111/ajt.16516.", "Meo SA, Bukhari IA, Akram J, Meo AS, Klonoff DC. COVID-19 vaccines: comparison of biological, pharmacological characteristics and adverse effects of Pfizer/BioNTech and Moderna Vaccines. Eur Rev Med Pharmacol Sci. 2021;25(3):1663-9. doi: 10.26355/eurrev_202102_24877."]}